The Japanese economy : its present phase and medium-term tasks - towards regaining strength for private enterprise- (Tokyo, Japan : Japan Federation of Economic Organizations (KEIDANREN))
The book attempts to project economic development for a medium term of three to five years cognizant of the realities of private industry and individual enterprises
osc 25/01/2019
Loans
Keywords: Economic situation; Japan